2021
DOI: 10.1002/lary.29473
|View full text |Cite
|
Sign up to set email alerts
|

Prematurity: A Prognostic Factor for Increased Severity of Pediatric Obstructive Sleep Apnea

Abstract: Objective/Hypothesis: Studies have suggested preterm birth, defined as gestational age (GA) <37 weeks, is a risk factor for obstructive sleep apnea (OSA) in later childhood. However, little is known about the characteristics, severity, and degree of intervention of childhood OSA in former preterm infants compared to term infants. This study compares polysomnographic characteristics and surgical interventions in former preterm and term infants presenting with sleep disordered breathing.Study Design: Retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…The associated increase in clinical monitoring and oximetry before PSG could have led to an increased pretest probability for OSA among infants who may have displayed sleep‐related oxyhemoglobin desaturations or other signs of SDB during inpatient monitoring. While prematurity has been previously identified as a risk factor for OSA, this was not identified within our cohort 30,31 . This could be due to the fact that there were approximately half as many children with trisomy 21 among those with premature birth ( N = 13) compared to those who were born at term gestational age ( N = 25).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The associated increase in clinical monitoring and oximetry before PSG could have led to an increased pretest probability for OSA among infants who may have displayed sleep‐related oxyhemoglobin desaturations or other signs of SDB during inpatient monitoring. While prematurity has been previously identified as a risk factor for OSA, this was not identified within our cohort 30,31 . This could be due to the fact that there were approximately half as many children with trisomy 21 among those with premature birth ( N = 13) compared to those who were born at term gestational age ( N = 25).…”
Section: Discussionmentioning
confidence: 67%
“…While prematurity has been previously identified as a risk factor for OSA, this was not identified within our cohort. 30,31 This could be due to the fact that there were A significant number of children were also diagnosed with CSA (N = 11, 12%). This finding may be related to the number of children with trisomy 21 in our cohort (N = 38, 43%), as an increased risk for CSA has been previously described in these children.…”
Section: Discussionmentioning
confidence: 99%
“…However, preterm delivery is a risk factor for obstructive sleep apnoea later in life. In a retrospective chart review of 615 patients, preterm neonates were at a 2.97‐fold greater risk for obstructive sleep apnoea, and more severe forms of obstructive sleep apnoea later in life than are full‐term infants 65 . However, this study did not specifically evaluate whether AOP was associated with a risk of later‐in‐life apnoea.…”
Section: Commentmentioning
confidence: 97%
“…Prior studies have suggested associations between prematurity and OSA. One study has shown that a history of prematurity is associated with increased AHI and diagnosis of severe OSA compared to children born at term [ 27 ]. In fact, the risk of OSA in children who are born prematurely is increased by 4–5 fold.…”
Section: Common Risk Factorsmentioning
confidence: 99%